Towards good lighting for the stage - Doshi, Marcus (New York, NY : Routledge, 2023)
"Towards Good Lighting for the Stage: Aesthetic Theory for Theatrical Lighting Design explores the theoretical underpinnings of effective lighting design from conceptualization to live performance. Through an investigation of the author's own aesthetic point of view-grounded in a broad investigation of art and design that blends pop culture and fine art, theory, and practice-this book documents the author's thinking on the design process to fill the unexplored gap between an aesthetic philosophy and its expression in composition. Re-definitions of the artist, artwork, and spectator link beauty and artistic efficacy to arrive at a set of principles for assessment that demand that contemporary lighting design surpass utilitarian visibility to become a vital part of the total artwork that is a theatrical production. Inspired by the movements of the broader art and design worlds of the mid-19th century through present day-citing influences as diverse as Jennifer Tipton, Lois Tyson, Dieter Rams, and Dave Hickey-this book charts a course from the artistic team's dramaturgical work to a solo studio concept to the tech table. Engaging and wide-ranging, Towards Good Lighting for the Stage synthesizes years of cross-disciplinary research and case studies of the author's own work into provocative reading for practitioners of lighting design, advanced students, and academics, as well as those interested in connecting theatrical practice, aesthetic theory, and visual art"--
Beauty -- Artist/artwork -- The spectator -- Theatre -- Theatrical abstraction -- On design -- The box -- Praxis -- Coda: So, now what?
Keywords: Stage lighting; Theaters -- Stage-setting and scenery; PERFORMING ARTS / Theater / Direction & Production